2016
DOI: 10.1016/j.neuropharm.2016.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive effects of eicosapentaenoic and docosahexaenoic acids in regulating neural stem cell fate are mediated via endocannabinoid signalling pathways

Abstract: Running title: EPA, but not DHA induces proliferation in NSCs Abbreviations: AA, Arachidonic acid, AEA, anandamide, DHA. Docosahexaenoic acid; EPA, eicosapentaenoic acid, 2-AG, 2-arachidonylglycerol 2 Title: Distinctive effects of eicosapentaenoic and docosahexaenoic acids in regulating neural stem cell fate are mediated via endocannabinoid signalling pathways Emerging evidence suggests a complex interplay between the endocannabinoid system, omega-3 fatty acids and the immune system in the promotion of brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 66 publications
1
34
1
2
Order By: Relevance
“…On the other hand, it is possible that some brain structures were protected from the effects of a moderate caloric restriction implemented only during pregnancy by the preferential uptake of the fetal tissues of specific LC-PUFAs, such as AA or n-3 PUFAs. It is interesting to note here that the n-3 PUFAs can affect the levels of endocannabinoids by decreasing their levels by competing for the metabolic enzymes [70, 84], or by increasing their levels depending on different circumstances [78, 85]. Additionally, the presence of sexual dimorphism mainly associated to the alterations found in olfactory bulb and the PEA levels in all the brain regions of females, suggest that the maternal calorie-restriction might have affected the male and female offspring through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is possible that some brain structures were protected from the effects of a moderate caloric restriction implemented only during pregnancy by the preferential uptake of the fetal tissues of specific LC-PUFAs, such as AA or n-3 PUFAs. It is interesting to note here that the n-3 PUFAs can affect the levels of endocannabinoids by decreasing their levels by competing for the metabolic enzymes [70, 84], or by increasing their levels depending on different circumstances [78, 85]. Additionally, the presence of sexual dimorphism mainly associated to the alterations found in olfactory bulb and the PEA levels in all the brain regions of females, suggest that the maternal calorie-restriction might have affected the male and female offspring through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations suggest competition for shared biosynthetic pathways as DHA and EPA displace ARA from membrane phospholipids. Interestingly, recent work in our laboratory found that acute administration of DHA or EPA significantly increased 2-AG, although not AEA levels in neural stem cells [73]. This increase may be driven by competition for the inactivating enzymes, such as COX-2, although further work is needed to fully elucidate the underlying mechanisms.…”
Section: Metabolism Of Pufa and Endocannabinoidsmentioning
confidence: 96%
“…DHA and EPA treatment has consistently been shown to increase adult hippocampal neurogenesis across a range of animal models [134], also in neural stem cells, where DHA appears to promote neuronal differentiation [73]. Similarly, the endocannabinoid system is essential for adult neurogenesis in both the hippocampus [135, 136] and SVZ [137], although studies into the pro-neurogeneic effects of endocannabinoids in the dentate gyrus have produced conflicting results.…”
Section: Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers reported that activation of nuclear receptors for which n-3 FAs are ligands (e.g., peroxisome proliferator-activated receptor alpha [PPARα]) protected mice from a reduction in AHN induced by whole-brain irradiation [48]. Additionally, evidence from cell culture studies suggests that EPA and DHA have distinct effects on neural stem cells; EPA seems to induce neural stem cell proliferation via direct effects on endocannabinoid pathways [49]. …”
Section: Effects Of Chemotherapy In the Brainmentioning
confidence: 99%